Pain from torture: assessment and management. (November 2019) - Amris, Kirstine; Jones, Lester E.; Williams, Amanda C de C.
Abstract: Introduction: Survivors of torture are for many reasons at particularly high risk for inadequate assessment and management of pain. Among the many health problems associated with torture, persistent pain is frequent, particularly pain in the musculoskeletal system. The pathophysiology underlying post-torture pain is largely unknown, but pain inflicted in torture may have profound effects on neurophysiology and pain processing. Methods: A narrative review of assessment and treatment studies, informed by clinical experience, was undertaken. Results: The clinical presentation in survivors of torture shares characteristics with other chronic primary pain syndromes, including chronic widespread pain. Unfortunately, such pain is often misunderstood and dismissed as a manifestation of psychological distress, both in specialist psychosocially oriented torture services and in mainstream health care. This means that pain is at risk of not being recognized, assessed, or managed as a problem in its own right. Conclusions: The available research literature on rehabilitation for torture survivors is predominantly targeted at mental health problems, and studies of effectiveness of pain management in torture survivors are lacking. Rehabilitation is identified as a right in the UN Convention on Torture, aiming to restore as far as possible torture survivors' health and capacity for full participation in society. It is therefore important that pain and its consequences are adequately addressed in rehabilitative efforts. This article summarizes the current status on assessment and management of pain problems in the torture survivor.